Determination of Trace Elements Concentration in Saba Banana Samples at Different Maturation Stages via ICP-MS - Sahadi, Nur Anisah; Basri, Hatijah (Enhanced Knowledge in Sciences and Technology, 2025)
Saba @ Pisang Nipah (Musa 'saba'), a hybrid banana variety, is valued for its export potential and nutritional properties. This study aimed to determine the concentrations of trace elements and evaluate their nutritional implications in Saba bananas at different ripening stages using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The analysis focused on detrimental elements such as arsenic (As), cadmium (Cd), chromium (Cr), and lead (Pb), which are known to pose health risks if consumed in excess. The findings revealed significant variations in these elements during ripening. Arsenic levels declined by 71.05%, from unripe (0.0038 mg/kg) to overripe (0.0011 mg/kg). Lead showed a 41.04% decline from unripe (0.0212 mg/kg) to overripe (0.0299 mg/kg), though it peaked in ripe bananas (0.0629 mg/kg). In contrast, chromium increased sharply, rising by 829.64% from unripe (0.0938 mg/kg) to overripe (0.8720 mg/kg). Cadmium levels rose by 80.00% from unripe (0.002 mg/kg) to ripe (0.0036 mg/kg) but decreased to 0.0026 mg/kg in overripe bananas. Despite these fluctuations, all trace element concentrations remained below the maximum permissible levels set by WHO/FAO Codex and EFSA, ensuring their safety for consumption. Nutritional analysis highlighted the benefits of ripe bananas, which contained the highest protein content (4.770 g/100g) and provided substantial energy (188 kcal/100g). Ripe bananas also had the highest carbohydrate content (47.0 g/100g), making them an energy-rich fruit. Dietary fiber, ash, and moisture contents remained consistent across all ripening stages (